The Three-point Problem of The Median Line Turning Point: on the Solutions for the Sphere and Ellipsoid - Sjöberg, Lars E. (The International Hydrographic Review, 2002)
The problem of determining turning points of median lines between states separated by sea is considered. The turning point is defined as the point with equidistance lines to two basepoints along the shoreline of one state and one basepoint in the adjacent state. For the sphere the equidistance lines are parts of great circles, and the problem is solved by closed formulas. For the ellipsoid the lines are defined along geodesics, and an iterative solution is presented.